236 Socioeconomic and Social Factors among Community-Dwelling Dependent Older People with Cognitive Impairment in Ireland. (16th September 2019) - Swan, Lauren; O'Sullivan, Maria; Warters, Austin; Irving, Kate
Abstract: Background: Dementia, and related cognitive impairment, is prevalent in dependent older adults in receipt of formal home care; importantly, this is a determinant of transition into long-term care (Aspell., 2019). Our study aimed to explore social and socioeconomic factors in community dwelling older people in receipt of formal home care. To our knowledge social deprivation has not been previously investigated in this population in Ireland. Methods: This study comprised a large cohort (n=1597) of community-dwelling adults aged 65 years or older who were in receipt of formal home care. Demographic, living setting, dependency (Barthel Index) were recorded; cognitive dysfunction (CD) included dementia and related cognitive impairment (Aspell., 2019). Social deprivation was captured by the Pobal HP Deprivation index which categorises affluence or disadvantage by residential area in Ireland. Results: The study population (n=1597) was of mean age 83.3 ± 7.2, supported by 11.1 ± 7.2 hours of home care per week and 10.8% and 31.7% were categorised as of disadvantaged and affluent deprivation status, respectively. Those who received home support in areas of disadvantage were significantly younger than in affluent areas (79.1 ± 7.3 v 85.6 ± 6.87 years, p< 0.001). Prevalence of CD was 43.3%. CD vs non-documented CD were characterised by a significantly higher proportion of females (66.5% v 61.4%, p <0.05), widowed (47.4% v 41.8%, p <0.05) and very disadvantaged (7.4% vs 5.0%, p <0.05). Furthermore, the CD group had a significantly higher falls risk but lower physical dependency (Barthel), lower requirement for mobility support and higher need for meal assistance. Home care hours were higher (11.6 ± 7.2 v 10.8 ± 7.2 p <0.001) for the CD group, and comprised generic, rather than dementia-specific support. Conclusion: The findings have implications for developing personalised dementia-specific home support and interventions. Further research is needed into disadvantaged deprivation and the need for home support at a younger age.